Documentation of three sponge species belong to the family of Petrosiidae - Qaralleh, Haitham; Syed Osman Idid, Syed Zahir Idid; Saad, Shahbudin; Darnis, Deny Susanti; Ezzat Mustafa, Basma (INSI Publications, 2011)
Taxonomic identification of organisms is the first and the most critical step in any research involving organisms. Four marine sponges collected from two different sites were identified based on their morphology, skeleton, and spicules characteristics. The description of each species was compared with the source description of sponges to identify the species. One of the sponge species investigated was identified as Neopetrosia exigua and two species were found to be Xestospongia testudinaria. Final identification of the species was assigned by experts. This simple identification may be useful to non-specialists as it is based on external or internal morphological characteristics.